Criminality, subject transgressor and collective fears in Lima and Callao - Carrillo Piraquive, Carlos Enrique (2017)
This article explores the emergence of the new Lima , it’s not only the subject emerging entrepreneur, but is also the subject offender who breaks the rule and violent to another, even with cruelty in a context of violence . In this regard organized crime and its various manifestations overflow and de- institutionalized society, criminality is amplified by the media , making collective fears in the population, associating crime and poverty , in short , install a culture of fear.